Potential Breeding Habitat for Forest Birds Suburbs - Natalie Pegg; Mark Hostetler (EDIS)
Studies report that urban areas may not provide breeding habitat for interior-forest birds, but some residential neighborhoods do have sufficient vegetation to serve as breeding habitat for forest birds and even interior-forest specialists. The authors investigated the occurrence of three interior-forest specialists, pileated woodpeckers, summer tanagers, and northern parulas, during the breeding season in two suburban neighborhoods of Gainesville, Florida, and found that all three species occurred in residential neighborhoods consistently throughout the breeding season and were most often detected in local areas with dense vegetation from the ground to the canopy. Our results suggest that decision-makers can improve the amount of breeding habitat in southeastern cities for these three species by retaining forest fragments, tree canopy, large trees, tree snags, and understory vegetation.